2022
DOI: 10.1136/bmjopen-2021-052280
|View full text |Cite
|
Sign up to set email alerts
|

Adverse childhood experiences and implications of perceived stress, anxiety and cortisol among women in Pakistan: a cross-sectional study

Abstract: ObjectivesAdverse childhood experiences (ACEs) are linked to poor maternal mental health. The goal of this study is to examine the associations between ACEs and multiple manifestations of stress (including perceived stress, anxiety and cortisol) among mothers in rural Pakistan.DesignThis study used a cross-sectional design. Mothers were originally recruited during their third trimester of pregnancy and followed until 36 months post partum. Cortisol was collected at 12 months post partum, and self-report data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 96 publications
1
6
1
Order By: Relevance
“…The connection between depression and anxiety and ACEs was well established in this study. The results of this study, while supporting previous reports that ACEs are associated with psychological disturbances, such as depressive feelings, stress, and anxiety [ 20 ], do not support a connection between ACEs and the development of physiological or medical disorders [ 14 ]. One explanation for this is related to the age group of this study; the majority of the sample were young people, which resulted in a lack of effect or connection between chronic illness and ACEs.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The connection between depression and anxiety and ACEs was well established in this study. The results of this study, while supporting previous reports that ACEs are associated with psychological disturbances, such as depressive feelings, stress, and anxiety [ 20 ], do not support a connection between ACEs and the development of physiological or medical disorders [ 14 ]. One explanation for this is related to the age group of this study; the majority of the sample were young people, which resulted in a lack of effect or connection between chronic illness and ACEs.…”
Section: Discussionsupporting
confidence: 81%
“…According to the researchers, poverty was a possible mitigation factor of the high experiences of ACEs among rural children [ 19 ]. Another study conducted in rural Pakistan found ACEs to be associated with higher levels of perceived stress, anxiety, and cortisol [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have shown that there is an association between ACEs and health problems in adulthood, such as obesity, mental disorders, high blood pressure 4, depression, diabetes, irregular sleep patterns 5, lung cancer, metabolic issues, in ammation, liver diseases 6 , and mental health issues 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Research conducted in sub-Saharan Africa (Amone-P' Olak & Letswai, 2020;Naicker et al, 2022) and Asia (Ikram et al, 2022;LeMasters et al, 2021), and other places around the globe (De et al, 2013;Zarse et al, 2019) illustrates consistent associations between exposure to ACEs and heightened mental health problems, diminished psychological well-being, and substance use. The current investigation drew on the developmental cascade theory to potentially explain associations between ACEs, well-being, and substance use.…”
mentioning
confidence: 99%
“…Furthermore, there is a growing literature linking ACEs and health behaviors, including maladaptive substance use and addiction (Zarse et al, 2019). However, despite the explosion of research on ACEs since the publication of Felitti et al’s (1998) seminal paper, as several researchers have noted, relatively fewer studies of ACEs have been conducted in sub-Saharan Africa (Amone-P’Olak & Letswai, 2020; Manyema & Richter, 2019; Naicker et al, 2022) or large parts of Asia, including Pakistan (Ikram et al, 2022; LeMasters et al, 2021). Reviews of prevalence rates of ACEs across countries have reported fewer ACEs on average in high-income compared to low- and middle-income countries (Hughes et al, 2017).…”
mentioning
confidence: 99%